Pré-tratamento organossolve da biomassa residual de eucalipto utilizando etanol - Souza, Liliana Bernardino de Oliveira e (2021)
The discussions about the use of fossil fuels, such as oil, are guided not only by its pollutant load but mainly because it is a non-renewable resource. As countries grow, societies become more dependent on technological advances, which increases the demand for energy and, consequently, increases the pressure on non-renewable resources. Many alternatives are currently being studied seeking to replace fossil fuels with renewable resources. Biomass is a viable, renewable and sustainable alternative not only for the production of biofuels but also as a platform for the manufacture of high value-added chemicals. Over the past decades, there has been an increase in studies involving the fractionation of lignocellulosic biomass in its polymers, cellulose, hemicellulose and lignin so that each constituent can be achieved generating commercialization products, through pretreatment methods, one of them being the organosolve pretreatment method that through a mixture with organic solvents/water at high temperatures, is able to deconstruct and fractionate the biomass, obtaining elements with a high degree of purity. The objective of this study was to perform the extraction of lignin from residual biomass of eucalyptus being proposed a factorial experimental planning 2 (3-0) in order to verify which variables, temperature (180°C, 200°C, 220°C), solvent concentration (50%, 60%, 70%) and reaction time (120min, 180min, 240min) are significant in the process of biomass delignification. In the organosolve pretreatment method a batch reactor was used in order to identify, at the end of each experiment, the delignified biomass (solid part) and the black liquor (liquid part). By High Performance Liquid Chromatography (HPLC) the black liquor was analyzed, and the extracted lignin was separated by acid precipitation and then characterized. The "in natura" and pre-treated biomass were characterized in relation to its chemical composition, using Xray diffraction equipment to identify its structure and crystallinity index, shape and aspect (Scanning Electron Microscopy - SEM). Then, the final yield and delignification content were obtained. Fourier Transform Infrared Spectroscopy (FTIR) was also performed in order to verify the constituent groups in the lignin polymer chain, allowing the identification of types of bonds and functional groups, thus being able to assess the main similarities with the standard commercial lignin (Sigma Aldrich).The experiments that showed the highest delignification were those characterized by higher temperature and higher ethanol concentration (220 °C; 70%), which means that at the highest temperature and higher ethanol concentration, greater biomass delignification occurs. In a visual analysis it was possible to notice very pronounced peaks that presented significant crystalline portion in relation to the biomass "in natura" and also the change in structure and aspects in the fibers of biomass after the organosolve pretreatment. The infrared analysis of the lignins showed spectra quite coincident when compared to commercial lignin, only, with small variations in the intensities of some peaks.